“Do centro para a margem”: Um estudo histórico-antropológico do processo de ascensão, declínio e reinvenção das cebs, o caso da comunidade São Benedito – Santa Rita/PB - Santos, Elenilson Delmiro dos (2016)
The religious scene that has established itself in Brazil in recent years, have demanded of religions, especially Catholicism, the need to put forth ruptures, conflicts, innovations, continuities and especially adoptions of new theologies in overcoming old. It is urgent prevail for pastoral models that are able to establish a close relationship with the new religious standards set by society. In effect, we are witnessing the affirmation of religious experiences, set by the traces of modernity, who preach the centrality of subjective and private sphere of religion. As a result, experiments such as Ecclesial Base Communities - CEBs for take hold in view of the collective and social character of religion, come into crisis. In this sense, this work is premised analyze the current situation of CEBs in Brazil, as suggested by the subtitle of our work, the process of the rise, decline and reinvention, and as a source of analysis a case study. Our theoretical option is for the concept of religious modernity, as worked out by Danièle Hervieu-Léger. As a research source, use of bibliographic production, arising from the fields of Sciences of Religions, Sociology, Anthropology and Theology. Thus, authors such as Faustino Teixeira, Leonardo Boff, José Comblin, among others, were of fundamental importance to the extent allowed us to better understand the elements that sustain and inspire the journey of CEBs. In analyzing the results of the field, the anthropological literature as Vagner Gonçalves, Roberto C. de Oliveira, among others, helped us to understand and cut the lines of our interviewees to collaborate with what was our interest in this study. As a result of research conducted in São Benedito community, city of Santa Rita/PB, obtained from the literature and the field itself some answers to the questions that inspired the construction of this work: there is still place for the CEBs in the current religious dynamics? Were they, in fact, the CEBs living a moment of reflux? Our results showed that the maintenance of CEBs in the Catholic religious scene, much depends on your own ability to renew themselves and interact with new social and religious demands.